A gestão do conhecimento como fator determinante no processo de inovação do setor produtivo: um estudo de caso na Petrobras - Pimenta, Rosângela Borges (2006)
The objective of the present study was to analyze the importance of the knowledge management dimensions as essential factors in the process of innovation of the productive sector. Seven dimensions were analyzed: strategy of the high administration, structure, culture, administration of human resources, learning with the environment, technology of information and the communication and measuring of the results. The study also searched for characterizing the importance of the organizational communication, as a crucial way for the creation, sharing, dissemination, transference and storage of knowledge in innovation environments. In relation to the evaluated aspects the study tried to identify the ones that facilitate and the ones that limit practical managerial development of the projects teams activities. The theoretical reference approaches the aspects related to knowledge, the management of knowledge, management of people, communication and the innovation. The instruments for collecting data had been documentary research, the questionnaire and the semistructuralized interview. The research, of exploratory character, was characterized as a case study. The methods used for the inferences have been the quantitative and qualitative analyses. The case study took place at Petrobras Center of Research. By crossing the information on the related instruments of compilation of data, it was possible to get to an ample vision of the knowledge management process of in a continuous innovation environment. In conclusion, the management of knowledge is a basic factor in the innovative process for the competitiveness of the organization.